PENGEMBANGAN MEDIUM BIOSTARTER KOMPOS FESES GAJAH DENGAN MEMANFAATKAN BAHAN BAKU LOKAL - , TRI SUNU DANE WIBAWA; , Nanung Agus F., S.Pt., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to determine the effect of medium biostarter for elephant dung compost quality. The treatment consists of elephant dung with the addition of rice bran biostarter medium (T1), pineapple biostarter medium (T2), and banana weevil biostarter medium (T3), they were composted for a month and turned once a week. pH and temperature measured every day during composting. Physical tests performed after 30 days of composting include moisture content, organic matter, C organic, N total, P total, K total, and C/N ratio